Endoscopic Urinary Diversion As Initial Management of Symptomatic Obstructive Ectopic Ureter in Infants - Ortiz, Ruben; Parente, Alberto; Burgos, Laura; Angulo, Jose Maria (Frontiers in Pediatrics, 2017)
Aim Definitive surgery of ectopic ureter in infants is challenging. We propose an endoscopic urinary diversion (EUD) as a novel surgical technique in the initial management of symptomatic obstructive ectopic ureter. Patients and methods Sixteen obstructive ectopic ureters (14 patients) were initially treated by EUD between 2006 and 2015. All patients had urinary tract dilatation worsening at preoperative US scans and at least two febrile urinary tract infection (UTI) or urinary sepsis despite antibiotic prophylaxis. Ectopic ureter was confirmed by cystoscopy. When ectopic meatus was not found, EUD consisted in the creation of a transurethral neo-orifice (TUNO) performed by needle puncturing of the ureterovesical wall, under fluoroscopic and ultrasound control. If ectopic meatus was identified in the posterior urethra, “intravesicalization procedure” was done opening the urethral–ureteral wall to create a new ureteral outlet into the bladder. Results EUD was done at a median age of 3.5 months (0.5–7) with median follow-up of 48 months (24–136). TUNO was performed in six patients and “intravesicalization” in eight patients. Significant differences were observed in ureteral diameter and anteroposterior pelvis diameter before and after endoscopic treatment (p < 0.005). Initial renal function was preserved in all cases. Postoperative complications were UTI in four patients and TUNO stenosis in one patient, treated by endoscopic balloon dilation. Definitive treatment was further individualized in each patient after 1 year of life. Conclusion EUD is a feasible and safe less-invasive technique in the initial management of symptomatic obstructive ectopic ureter. It allows an adequate ureteral drainage preserving renal function until definitive repair if necessary and does not invalidate other surgical options in case of failure or future definitive treatments.